DEVELOPING LOCAL WISDOM BASED SCIENCE LEARNING DESIGN TO ESTABLISH POSITIVE CHARACTER IN ELEMENTARY SCHOOL - Subali, B.; Sopyan, A.; Ellianawati, Ellianawati (Physics Department, Faculty of Mathematics and Natural Sciences, Semarang State University, 2015)
This study aims to design a science learning program based on the local wisdom and apply it in elementary school. Mixed method research was use to gain the significance improvement from the design. There were 35 elementary science teachers from 16 elementary schools chosen by using purposive random sampling. The previous research revealed that there are about 80% of the teachers who were recognized the local wisdoms in their environment, but none of them have a capability to use it as a part of their science program in the classroom. To overcome this constrain, Review(R), Task(T), Solution(S), Reflection(R), and Evaluation(E) design was proposed in elementary school science learning. By implementing the design in two elementary schools, 11 positive characters expected were indicated from studentsâ performance. But characters of honest, disciplined, conscientious, diligent, careful, responsibility, and caring environment, are most significant.Â Tujuan dari penelitian ini adalah mengembangkan desain pembelajaran sains berbasis kearifan lokal pada tingkat sekolah dasar. Metode penelitian campuran (mixed method) digunakan untuk melihat signifikasi capaian pengembangan desain. Penelitian ini melibatkan 35 guru dari 16 sekolah dasar yang dipilih secara acak dari sekolah-sekolah yang memenuhi kriteria yang telah ditetapkan. Dari penelitian sebelumnya diperoleh hasil bahwa sekitar 80% dari sampel telah mengenali kearifan lokal di lingkungan sekolah masing-masing. Namun, tidak satupun dari sampel yang memiliki kapasitas untuk mengaplikasikan kearifan lokal tersebut ke dalam kurikulum sains mereka. Untuk mengatasi kendala ini, maka digagaslah desain Review(R), Task(T), Solution(S), Reflection(R), dan Evaluation(E) ini. Dua sekolah dipilih secara purposive sampling sebagai kelas eksperimen. Dengan mengkombinasikan dari kualitatif hasil RnD desain dan data kuantitatif nilai tes, diperoleh informasi bahwa 11 karakter positif terindikasi pada performan siswa. Dari kesebelas karakter tersebut, kejujuran, keingintahuan, jujur, hati-hati, tanggung jawab, dan peduli lingkungan yang paling meningkat secara signifikan. Â